Penerapan Sistem Electronik Traffic Law Enforcement (ETLE) dalam Penindakan Pelanggaran Lalu Lintas di Wilayah Hukum Polda Jatim - Narullita, Endang Sri (VISA: Journal of Vision and Ideas, 2024)
To keep up with technological developments, the National Police has issued a new system for enforcing traffic rules called ETLE (Electronic Traffic Law Enforcement). ETLE is an information technology-based traffic law enforcement system that uses electronic devices in the form of cameras that can detect various types of traffic violations and provide motor vehicle data automatically (automatic number plate recognition). ETLE camera footage can be used as evidence in cases of traffic violations. The use of ETLE is also a form of Polri's contribution in realizing East Java Province as a smart city and is in line with bureaucratic reform. Another benefit is increasing the culture of public order in traffic, which is a deterrent effect of the ETLE system. The main problem that will be discussed in writing this thesis is How effective is the enforcement of traffic violations using the Electronic Traffic Law Enforcement (ETLE) system at the East Java Regional Police? What are the obstacles in implementing the Electronic Traffic Law Enforcement (ETLE) system against traffic violators at the East Java Regional Police? and What is the role of the East Java Regional Police Traffic Directorate in providing solutions in implementing traffic violation law enforcement with Electronic Traffic Law Enforcement (ETLE)? This research uses a type of Empirical Legal Research, namely a legal research method that uses empirical facts taken from human behavior, both verbal behavior obtained from interviews and real behavior through direct observation. The East Java Police Traffic Directorate plays a role as an innovator in developing a law enforcement system for traffic violations using an information technology approach. ETLE can be said to be a method of prosecuting violations that has a positive impact on reducing the number of traffic violations.